Enhancing production efficiency through optimizing plant density in maize–soybean strip intercropping - Li, Guanghao; Liang, Yuwen; Liu, Qiannan; Zeng, Jinghan; Ren, Qingming; Guo, Jian; Xiong, Fei; Lu, Dalei (Frontiers in Plant Science, 2024)
Introduction Due to limited arable land resources, intercropping has emerged as an efficient and sustainable production method for increasing total grain yield per unit land area. Maize–soybean strip intercropping (MSSI) technology is being widely promoted and applied across China. However, the combination of optimal density for achieving higher production efficiency of both soybean and maize remains unclear. The objective of this study was to evaluate the differences in yield, economic benefits, land, and nitrogen (N) efficiency in MSSI systems under different densities. Methods Five maize/soybean density combinations (67,500/97,500 plants ha−1, D1; 67,500/120,000 plants ha−1, D2; 67,500/142,500 plants ha−1, D3; 60,000/142,500 plants ha−1, D4; 52,500/142,500 plants ha−1, D5) were set under the same N input in the field experiment. Results and discussion The results demonstrated that optimizing the density in the intercropping system could enhance production efficiency. Increasing the density of soybean and maize significantly increased the total grain yield (D3 > D2 > D1 > D4 > D5). The D3 treatment, exhibiting the best comprehensive performance, also promoted increases in leaf area index, dry matter accumulation, and N absorption and utilization. Path analysis indicated that density had the most substantial impact on maize yield, while grain number had the greatest influence on soybean yield, with contribution rates of 49.7% and 61.0%, respectively. These results provide valuable insights into optimal field density for summer planting in MSSI, facilitating its wider adoption.